Análisis Multitemporal De Los Cambios En Las Coberturas De La Tierra De Las Canteras Del Fallo De Acción Popular Nº 2009 00115 De 2018 De La Localidad De Ciudad Bolívar, Bogotá D.C., Colombia (2025)
In this study, a multitemporal analysis was carried out on the coverage of the Ciudad Bolívar locality where the quarries that are part of the Popular Action Ruling 2009-00115 of 2018 are located. This ruling includes 11 quarries located in the Ciudad Bolívar locality - Bogotá D.C., which are listed below: Villa Gloria Quarry, La Quebrada Quarry, La Pisinga Quarry, La Esperanza Quarry, Las Tolvas Quarry, Los Sauces Quarry, Limas Quarry, Porvenir Quarry, Jorge Monastoque Quarry, Juan Borda Quarry and Humberto Abella Quarry.